Estudo retrospectivo sobre a variação pós-operatória do escore de Gleason do adenocarcinoma prostático e fatores correlacionados - Zanettini, Luis Felipe Snel (2015)
Introduction: Currently about 23% of cancers diagnosed in males are prostate adenocarcinoma (PA). Because of the indolent behavior observed in the early stages of PA, less invasive treatment methods are being used in an attempt to minimize comorbidities related with conventional treatments. After prostate needle biopsy tissue (BX) and histological analysis, the Gleason score (GS) is obtained. The GS alone is able to predict the prognosis of patients with PA and is used, along with other variables, for choosing the therapeutic option. Studies have shown variations in the postoperative GS in up to one third of cases. Objective: Identify the variation of the GS in cases of PA before and after radical prostatectomy (RP) and correlate to prostate volume, preoperative serum value of Prostate-Specific Antigen (PSA), age and PSA density (PSAd). Method: A retrospective, cross-sectional study of 279 cases submitted to RP due to PA between January 2008 and June 2013, assessing the postoperative variation of the GS, and performing correlation analysis of postoperative GS elevation with age, prostate volume, the preoperative PSA and PSAd, in a continuous and categorical manner. Results: The mean age, prostate volume, serum PSA and PSAd were, respectively, 63.8 years-old, 8.8 ng/ml, 33.37 cm3 and 0.32ng/mL/cm3. Postoperative GS variation was observed in 34% of the cases, with 27% having higher and 7% having lower values. When the GS was 6 or lower, 29% of all patients presented with an increase in postoperative GS values. Patients age and prostate volume were not statistically significant in postoperative GS elevation (p = 0,42 and p = 0,37, respectively). Preoperative serum PSA value demonstrated correlation with postoperative elevation of GS (p = 0.007), as a protection factor when less than 4 ng/mL (OR 0.41, p = 0.05) and as a causal factor when greater than 10 ng/mL (OR 2.62, p = 0.0008). The PSAd also proved to be related to postoperative elevation of the GS (p = 0,002), as a protection factor when less than 0,15 ng/mL/cm3 (OR 0,41 and p = 0,02) and as a causal factor when greater than 0,15 ng/mL/cm3 (OR 2,39 and p = 0,02). Conclusion: GS variation occurred in 34% of all cases, with 27% of patients having higher scores and 7% having lower scores. The high PSA value and the PSAd were associated with postoperative increase of GS values.